Apoptosis Inducing Effects of Venomous Glandular Extract from Heterometrus spinifer in HepG2 Cells - Kong, Ivan; Wei, Ong Khang; Singh, Nivrenjeet; Singh, Nisheljeet (International Journal of Scientific Research in Biological Sciences, 2021)
In the search of alternative anti-cancer chemotherapeutic drugs, until recently, scorpions’ venom is one of the most promising sources which were highly sought-after. From previous studies, scorpions’ venom demonstrated promising inhibitory effect on cell proliferation and led to apoptosis in various cancer cells. In this study, we investigated the effects of Heterometrus spinifer scorpion venom on HepG2 cells (liver cancer) to explore its anti-cancer effect in the aspects of inhibition of cell proliferation, apoptosis induction and tumor genes expression. MTT assay revealed that H,spinifer’s venom induces cytotoxicity in HepG2 cells. Hoechst 33342 stained the condensed DNA caused by apoptosis in the cells treated with the venom. At the same time, propidium iodide stained the dead HepG2 cells with ruptured cell membranes. These findings showed a dose- and time-dependent cell death induced by the H.spinifer’s venom. Furthermore, TUNEL assay demonstrated the fragmentation of DNA in the venom-induced apoptotic HepG2 cells by a dose-dependent manner. Consistently, RT-PCR findings showed up-regulated expression levels for both capsase-3 and p53 tumor protein genes, explaining the cause of apoptosis and cell death. Taken together, these results highly suggest that Heterometrus spinifer’s venom can be a potential source of apoptosis-inducing agent.